Recruiter's perception of artificial intelligence (AI)-based tools in recruitment - Piotr Horodyski (Computers in Human Behavior Reports, 2023)
Artificial intelligence (AI) technologies have advanced to the point where they can automate large parts of the hiring process and in consequence transform the role of recruiters or Human Resource professionals. However, there is little research on how recruiters perceive AI, and little is known about the motivations or factors that influence the use of AI in their workplaces. This study examined recruiters' intentions to use AI by extending the unified theory of acceptance and use of technology (UTAUT) to include the frequency of AI use and education. Data were obtained from a web-based survey with 238 demographically balanced participants. Hierarchical regression analysis was applied for data analysis and hypothesis testing. The results showed that behavioral intention was significantly and positively influenced by performance expectancy, and the moderating effect of frequency of AI use, while gender, age, experience, and education had no significant impact. Efficiency gains, time savings and automation emerged as the most important benefits, while lack of human judgment was the main disadvantage of AI use in recruitment.